043 Effect of a patient education programme on quality of life in patients with chronic heart failure. (23rd September 2015) - Seronde, M F; Nicolas, M; Descotes-Genon, V; Chopard, R; Dutheil, J; Briand, F; Bernard, Y; Schiele, F
Abstract : Background and Objectives: Heart failure is a major public health issue in France. To deal with the complex management of this disease, therapeutic patient education (TPE) programmes have been developed over recent years which focus on optimising patient autonomy and self-management. Several studies have shown that TPE programmes help reduce the number of hospital readmissions and the length of hospital stay, as well as the overall costs associated with the disease. In 2004, a TPE centre for patients with chronic heart failure (CETIC) was established in the cardiology outpatients department of Besançon university hospital. It is staffed by a multidisciplinary team. The aim of this study was to evaluate the efficacy of TPE in improving patients' quality of life. Programme: Participation in TPE was on an outpatient basis and started at least 1 month after discharge. Individual and group sessions were held by a multidisciplinary team comprising a nurse, a cardiologist and a dietician. During the group sessions, four themes were discussed: chronic heart failure and warning signs, treatment; low-salt diet and physical activity. Patients were seen at the start of the programme, then once every month for 4 months, and finally, 6 months after the end of the programme. The main endpoint was quality of life as measured by the Minnesota questionnaire at the start and 6 months after the end of the programme. Results: A significant improvement was observed in the quality of life of patients with chronic heart failure who participated in TPE. The overall Minnesota score decreased from 37.6±24 before the programme to 26±18 after the programme (p<0.0001), the physical dimension score decreased from 17 to 12 (p<0.0001) and the emotional dimension from 6 to 4 (p<0.0001). The clearcut improvement in quality of life, especially for the physical dimension, was mainly due to a reduction in dyspnea, asthenia and in difficulties with activities of daily life, walking and climbing stairs. This improvement in quality of life should help contribute towards reducing further episodes of decompensation and subsequent readmission to hospital. Discussion and Conclusion: Despite progress in the management of chronic heart failure, the prognosis is unfavourable, with a mortality rate of about 50% at 1 year for the most advanced stages of the disease. In general, hospital admissions increase as the disease progresses. One patient in two is readmitted to hospital within 1 year of decompensation. Chronic heart failure is the main cause of hospital admissions in patients aged over 65 years. Half of the admissions are due to avoidable causes, such as low compliance with treatment and lifestyle guidelines, or inappropriate follow-up. Several studies have shown that specific interventions on modifiable risk factors can help reduce the number of decompensation episodes and thus hospital readmissions. TPE programmes help improve quality of life, functional status, tolerance for physical activity, as well as compliance with treatment and a low salt diet. In conclusion, TPE programmes should be a cornerstone of the management of patients with chronic heart failure with a view to improving their quality of life and encouraging better self-management of disease. TPE improves compliance with treatment and lifestyle recommendations, and can thus contribute to delaying and/or avoiding adverse events and improving prognosis. The participation of a multidisciplinary team is essential. Objectif(s), contexte: L'insuffisance cardiaque (IC) constitue un problème de santé publique majeur en France. Pour faire face à la complexité de la prise en charge, des programmes d'éducation thérapeutique (ET) se sont développés au cours de ces dernières années, centrés sur la relation éducative où le patient devient plus autonome et responsable. En effet, plusieurs études ont montré que la prise en charge des patients en ET réduisait le nombre et la durée des hospitalisations ainsi que le coût de la maladie. Au CHU de Besançon, un Centre d'Education Thérapeutique pour les patients Insuffisants Cardiaques (CETIC) a été créé en novembre 2004 à l'hôpital de jour de cardiologie, où les patients bénéficient d'une prise en charge multi-disciplinaire. L'objectif de ce travail est d'évaluer l'efficacité de l'ET sur la qualité de vie. Programme: Prise en charge en ET en ambulatoire, au moins 1 mois après la sortie de l'hôpital. Séances d'ET en individuel et en groupe, assurée par une équipe multidisciplinaire comprenant une infirmière, un médecin cardiologue et une diététicienne. Lors des ateliers de groupe, les quatre thèmes suivants sont abordés : la maladie et les signes d'alerte, les traitements, l'alimentation hyposodée et l'activité physique. Les patients sont vus au début du programme d'ET, ensuite une fois par mois pendant 4 mois, et à 6 mois après la fin du programme. Le critère principal d'évaluation est la qualité de vie, mesurée par le questionnaire Minnesota au début et 6 mois après la fin du programme. Résultats: Une nette amélioration de la qualité de vie a été observée chez les patients qui ont participé au programme de qualité de vie (score Minnesota brut avant 37, 6±24 vs 26±18 après, p<0, 0001; score physique moyen 17 avant vs 12 après, p<0, 0001; score mental moyen 6 avant vs 4 après, p<0, 0001). Impact clinique: Amélioration de la qualité de vie des patients insuffisants cardiaques, particulièrement sur la dimension physique, avec réduction notamment de la dyspnée, de l'asthénie, de la gêne occasionnée par les activités de la vie quotidienne ou par la marche ou la montée des escalier. On peut imaginer que cette amélioration de la qualité de vie contribue à réduire le nombre de ré-hospitalisations parmi ces patients. Discussion: Malgré les progrès thérapeutiques, le pronostic des patients en insuffisance cardiaque chronique reste sombre avec une mortalité de l'ordre de 50% dans l'année aux stades les plus avancés. L'évolution est marquée par un grand nombre de ré hospitalisations. Un patient sur deux sera ré hospitalisé dans l'année suivant une première décompensation, ce qui fait de l'IC le premier motif d'hospitalisation des sujets de plus de 65 ans. D'autre part, la moitié des hospitalisations serait due à des causes évitables: mauvaise observance du traitement et des règles hygiéno-diététiques, ou suivi mal organisé. Il a été montré dans la littérature que des interventions spécifiques du type éducation thérapeutique visant les facteurs de risque modifiables peuvent aider à réduire le nombre d'épisodes de décompensation et ré-hospitalisation. L'ET améliore la qualité de vie, le stade fonctionnel ; la tolérance à l'effort tout en améliorant la compliance au traitement et au régime hyposodé. Conclusion: L'éducation thérapeutique doit faire partie intégrante de la prise en charge des patients en insuffisance cardiaque chronique afin d'améliorer leur qualité de vie et leur permettre de mieux gérer leur maladie de façon autonome. L'ET permet d'obtenir une meilleure compliance au traitement, et ainsi peut contribuer à retarder, voire éviter les événements adverses et améliorer le pronostic. L'implication de professionnels multi-disciplinaires est importante.